2020
DOI: 10.1055/s-0040-1716356
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after Multiligament Knee Injury Reconstruction using Novel Graft Constructs and Techniques

Abstract: Clinical outcomes after reconstruction for multiligamentous knee injury (MLKI) can be consistently favorable. However, recent implants and technique advances may allow for improvement in outcomes. Our institution has developed novel graft constructs and techniques for reconstructions with preclinical data supporting clinical use. Our study purpose was to assess clinical outcomes after reconstruction for MKLI using our constructs and techniques. Overall success rate, failure/revision rates, return to work (RTW)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…As a result of the database searches, 1285 potentially eligible studies were identified, of which 89 duplicate studies were detected. After duplicate studies removed, 1,196 studies were scanned using titles and abstracts, 72 studies were included in the full‐text review to evaluate if they met the inclusion criteria, and 36 studies ultimately found to meet study eligibility criteria and were included in the systematic review and meta‐analysis [1, 2, 4–17, 19–23, 26, 29, 32–36, 41–44, 46, 47, 49, 50] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the database searches, 1285 potentially eligible studies were identified, of which 89 duplicate studies were detected. After duplicate studies removed, 1,196 studies were scanned using titles and abstracts, 72 studies were included in the full‐text review to evaluate if they met the inclusion criteria, and 36 studies ultimately found to meet study eligibility criteria and were included in the systematic review and meta‐analysis [1, 2, 4–17, 19–23, 26, 29, 32–36, 41–44, 46, 47, 49, 50] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Postoperative stiffness was defined as limited range of motion (ROM) requiring arthroscopic arthrolysis surgery and/or manipulation under anesthesia (MUA) [5]. MLKI surgeries were defined as MLKIs operated on less than 3 weeks following injury in this meta‐analysis [13, 22].…”
Section: Methodsmentioning
confidence: 99%
“…The tibial fixation aspect in LaPrade’s technique aims to provide a more anatomic reconstruction but has also to be seen as a more invasive procedure. Additional preparation and establishment of the tibial drill tunnel presents additional trauma (and risk of collision with a tibial drill tunnel of the PCL graft), while the larger number of grafts increases scar tissue formation and therefore risk of reduced flexibility and arthrofibrosis [ 34 , 35 ]. This aspect is confirmed by the reduced maximum flexion angles of group B patients after 12 months (126.60° ± 4.22° vs. 134.17° ± 3.76°; p = 0.021).…”
Section: Discussionmentioning
confidence: 99%
“…Based on these and other preclinical data, these constructs and techniques have been applied at our institution and resulted in safe and effective management of a wide variety of MLKIs across a spectrum of patients. 30…”
Section: Discussionmentioning
confidence: 99%